1969
DOI: 10.1039/tf9696501121
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic oxidation of methane over noble metals

Abstract: The complete oxidation of methane over palladium, platinum, rhodium and iridium has been studied using a microcalorimetric technique. The results indicated that methane may be adsorbed on two types of reaction site, one of which also adsorbs oxygen. The activation energies are proportional to the Pauling bond energies of the oxygen-metal bond in the region where the order in oxygen is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…It has been reported that partial oxidation products are not observed during the oxidation of CHI over bulk noble metals (Yu Yao, 1980;Firth and Holland, 1969a). However, the formation of HCHO, CO, and H2 during the oxidation of CHI over Pd/A1203 catalysts at temperatures lower than 400 "C has also been reported (Cullis et al, 1971).…”
Section: Rerults and Diecursionmentioning
confidence: 91%
“…It has been reported that partial oxidation products are not observed during the oxidation of CHI over bulk noble metals (Yu Yao, 1980;Firth and Holland, 1969a). However, the formation of HCHO, CO, and H2 during the oxidation of CHI over Pd/A1203 catalysts at temperatures lower than 400 "C has also been reported (Cullis et al, 1971).…”
Section: Rerults and Diecursionmentioning
confidence: 91%
“…In particular, the mechanism involved in the oxidation of CH 4 on palladium surfaces is still very much a matter of debate [17]. Some authors refer to a Langmuir-Hinshelwood type adsorption mechanism [8,12,[18][19][20], whereas others propose a Mars and van Krevelen type redox mechanism [13,3,[21][22][23][24][25][26][27], or an Eley-Rideal type mechanism [28]. It could be argued that these discrepancies are due to the lack of understanding of the dynamic phenomena occurring on the surface of the catalyst during the catalytic combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical point of view, catalytic oxidation of methane is of increasing importance in exhaust aftertreatment (emissions from, e.g., natural gas fuelled engines, and homogeneous charge compression ignition and exhaust gas recycling combustion contain methane) as well as energy conversion processes. Although the reaction has attracted attention for decades [1][2][3][4][5][6], the understanding of elementary key-steps and the corresponding kinetics is still far from complete. Here, on the basis of temperature programmed and pulse-response oxidation experiments with Pt/Al 2 O 3 monolith catalysts previously carried out in our laboratory [6], a microkinetic model for simulations of the methane oxidation over alumina supported platinum has been constructed.…”
Section: Introductionmentioning
confidence: 99%
“…The complete oxidation of methane on platinum is of considerable interest because it is one of the generic catalytic reactions [1]. From a practical point of view, catalytic oxidation of methane is of increasing importance in exhaust aftertreatment (emissions from, e.g., natural gas fuelled engines, and homogeneous charge compression ignition and exhaust gas recycling combustion contain methane) as well as energy conversion processes.…”
Section: Introductionmentioning
confidence: 99%